Abdominal Cocoon Secondary to Meconium Peritonitis in a Neonate: A Case Report - Safwan Ahmad; Kanchan Kayastha; Sana Javed; Arsalan Wasti (EL-Med-Pub, 2013)
Abdominal cocoon is a complete or partial encasement of intestines and rarely viscera by a fibrocollagenous sac which is usually formed by a nonspecific chronic inflammatory reaction. We report a case of abdominal cocoon in a 2-day-old neonate presenting with intestinal obstruction.